A Analisis Sifat Fisikokimia, Farmakokinetik, Dan Toksisitas Senyawa Aktif Dalam Jahe Merah (Zingiber Officinale Var Rubrum Rhizoma) - Maulida, Masita Zumna; Ummahati, Daril; Muna, Laili Nailul (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Background:  Red ginger (Zingiber Officinale Var Rubrum Rhizoma) contains secondary metabolites that show pharmacological activity. However, not many know that Red ginger rhizome includes a compound produced as an anti-inflammatory. Objective:  This research aims to provide an initial screening by looking at the potential of the compounds produced by red ginger rhizomes Method: This research was carried out descriptively using ChemDraw software and then analyzed the physicochemical properties of the compounds. Next, the predictor servers, namely Lipinski and PreADMET, are used to see the pharmacokinetic characteristics. Meanwhile, to analyze the toxicity using Toxtree software. Result:  Based on the analysis, distinct physicochemical compounds are best: zingerone (period boil, period melted, a period critical temperature, and point necessary pressure) and zingiberene (Log P and gibs energy). Analysis results in Lipinski show geraniol, zingiberene, zingerone, and 1.8 cineol compounds criteria Lipinski. Besides That, pharmacokinetic data show the fourth compound has its solubility in high water. The intestinal absorption values of geraniol, zingiberene, zingerone, and 1.8 cineol are excellent. The compounds geraniol, zingiberene, zingerone, and 1.8 cineol all have good permeability to the blood-brain barrier, but of the four compounds, the compound with the best permeability is zingiberene. Conclusion: All compounds show a level of low toxicity for using skin and no toxicity for the heart.